Neuroprotective and Anticarcinogenic Properties of Hericium Mushrooms and the Active Constituents Associated with These Effects: A Review - Chen, Zhixia (Grace); Bishop, Karen Suzanne; Zhang, Jingying; Quek, Siew Young (Food Science and Engineering, 2022)
Hericium mushrooms are well known for their numerous medicinal benefits, of which neuroprotective and anticarcinogenic characteristics are two of the most reported properties. This review summarizes the research advances and techniques used to study these two advantages of Hericium mushrooms reported in the latest 20 years, namely between the years 2001 and 2021. Based on published research, the Hericium-unique compounds (e.g., hericenones and erinacines) and polysaccharides are the main active constituents associated with these two properties. It was reported that about 70 such secondary metabolites were characterized to help prevent or treat neurological and tumor diseases. We have collated the above information in order to provide insights for further studies aiming to maximize the application of Hericium mushrooms as functional ingredients for neuroprotection and anticarcinogenesis.